(untitled) (Archive of Conferences, 2020)
The thesis is devoted to the observe study of component types of diplomatic discourse – the speech of a president, the speech of a diplomat, the speech of representatives of diplomatic corpus, the diplomatic speech during an official visit, the speech of foreign tourists and diplomatic documents and syntagmatic relations of their lexis. The introductory part of the thesis examined the possibilities of diplomatic discourse in Uzbek linguistics, the existing problems in the field of research. The main part explores the character, structure, meaning and function of each types of diplomatic discourse. At the conclusion has demonstrated results of syntagmatic relations of their lexemes.